2014
DOI: 10.1007/s11524-013-9856-1
|View full text |Cite
|
Sign up to set email alerts
|

Material Deprivation Affects High Sexual Risk Behavior among Young People in Urban Slums, South Africa

Abstract: Young people in urban slums adopt HIV risk behaviors influenced by their neighborhood factors. Three critical factors in urban slums of Southern and Eastern Africa-the region most affected by the HIV epidemic in the world-are unmet needs of housing, food, and health care, which are associated with HIV sexual risks. Yet, there has been limited attention on how the combination of unmet needs of housing, food, and health care-i.e., material deprivation-relates to sexual risk behavior among young people in urban s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
(50 reference statements)
1
28
0
Order By: Relevance
“…Another explanation is that poverty, as measured by unemployment or other forms of financial distress, constrains young women's livelihood options requiring many of them to resort to exchanging sex for money, housing, or other commodities [14, 21-25]. Previous research has also shown that financial distress, including debt, income instability, lower earned income, food insufficiency, and large material transfers, have all been associated with higher rates of unprotected sex, inconsistent condom use, multiple sex partners, and sex exchange among women [6, 13, 26, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…Another explanation is that poverty, as measured by unemployment or other forms of financial distress, constrains young women's livelihood options requiring many of them to resort to exchanging sex for money, housing, or other commodities [14, 21-25]. Previous research has also shown that financial distress, including debt, income instability, lower earned income, food insufficiency, and large material transfers, have all been associated with higher rates of unprotected sex, inconsistent condom use, multiple sex partners, and sex exchange among women [6, 13, 26, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…Although not mentioned in our FGDs, other studies have found young people are also at risk for coercive sex if they are from materially deprived households [28]. Several other studies across Africa [2931] have also showed a relationship between material deprivation and high risk sexual behavior. Interventions for HIV prevention among vulnerable groups should also include programs for economic empowerment and job creation to reduce material deprivation and unemployment.…”
Section: Discussionmentioning
confidence: 63%
“…One implication is that developing gender-specific strategies that integrate traditional and behavioral economics into combined prevention technologies may better enable urban poor youth to reduce HIV risk. There has been increasing recognition of the inadequate programmatic response to the role of economic context on HIV risk in urban poor settings [83, 84]. From a traditional economics perspective, this means recognizing that both male and female youth are “rational” in maximizing their wealth and may be more likely to adopt preventive technologies when conflicting financial goals are less prominent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that poverty-related factors such as debt, unemployment, income and food insecurity, as well as absence of financial support have all been associated with engagement in sexual behaviors that increase risk of acquiring HIV [919]. These behaviors include unprotected sex [1014], inconsistent condom use [15], transactional sex [14, 1618], and multiple sexual partners [14, 18, 19]. Public health scientists have proposed several potential pathways between poverty and HIV, including misinformation within impoverished communities regarding condom use [20, 21], lack of resources to afford or negotiate condom use [21, 2225], or reliance among lower-income residents on transactional sex due to limited other livelihood activities [2631].…”
Section: Introductionmentioning
confidence: 99%